A PARADIGM SHIFT IN HIGHER EDUCATION TEACHERS’ TEACHING STYLE - Mičiulienė, Rita; Čiučiulkienė, Nijolė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The shift in the educational paradigms, changing the conceptual foundations of studies, forces us to take a closer look at the ability of Lithuanian higher education teachers to establish in practice the new education paradigm modelled on the theoretical foundations of the reform. The study investigates the teaching styles of higher education teachers (N 297) in four universities of applied sciences and the correlation between teachers’ teaching style, demographic factors and self-assessed didactic competence. The study findings led to the conclusions highlighting the following statements: although there is no prevailing teaching style, most college teachers work employing the interaction paradigm. The results also indicated that women show more support to learning paradigm than men; young teachers (25-35 years old) having assistant positions prefer  the teaching paradigm more than teachers of other age and position groups; the representatives of technological sciences are more inclined to the teaching paradigm, while humanities – to interaction paradigm; the teachers who assess their didactic competence highly follow the interaction paradigm in their teacher-student relationship, and low - the teaching paradigm. Though the findings of this study allow capturing a larger shift towards the interaction paradigm, teacher continuing development programmes and support are necessary for higher education teachers. The further research is needed to deepen and extend the findings of this study as well.